Mediation of the relationship between proteinuria and serum phosphate: Insight from the KNOW-CKD study - Jung, Ji Yong (PLoS One, 2020)
Proteinuria and hyperphosphatemia are risk factors for cardiovascular disease in patients with chronic kidney disease (CKD). Although the interaction between proteinuria and the serum phosphate level is well established, the mechanistic link between the two, particularly the extent to which this interaction is mediated by phosphate-regulating factors, remains poorly understood. In this study, we examined the association between proteinuria and the serum phosphate level, as well as potential mediators, including circulating fibroblast growth factor (FGF23)/klotho, the 24-h urinary phosphate excretion rate to glomerular filtration rate ratio (EP/GFR), and the 24-h tubular phosphate reabsorption rate to GFR ratio (TRP/GFR). The analyses were performed with data from 1793 patients in whom 24-h urine protein and phosphate, serum phosphate, FGF23, and klotho levels were measured simultaneously, obtained from the KoreaN cohort study for Outcome in patients With Chronic Kidney Disease (KNOW-CKD). Multivariable linear regression and mediation analyses were performed. Total, direct, and indirect effects were also estimated. Patients with high serum phosphate levels were found to be more likely to exhibit greater proteinuria, higher FGF23 levels, and lower klotho levels. The 24-h EP/GFR increased and the 24-h TRP/GFR decreased with increasing proteinuria and CKD progression. Simple mediation analyses showed that 15.4% and 67.9% of the relationship between proteinuria and the serum phosphate level were mediated by the FGF23/klotho ratio and 24-h EP/GFR, respectively. Together, these two factors accounted for 73.1% of the relationship between serum markers. These findings suggest that proteinuria increases the 24-h EP/GFR via the FGF23/klotho axis as a compensatory mechanism for the increased phosphate burden well before the reduction in renal function is first seen.